Improving Effective Communication Competence Through Team Building Training in Nursing Students: Quasi Eksperimen Study - Nur Sriyanti; Lisa Musharyanti (Indonesian Journal of Global Health Research, 2025)
To support the learning process of North Kalimantan Polytechnic nursing students regarding effective communication in cognitive and psychomotor aspects within the scope of patient safety, namely SBAR, a learning method is needed that is considered capable of meeting these two aspects. Team Building Training is a learning method in the form of training that provides a complete package of the latest learning methods because it can improve effective communication, train team cohesion and learn how to solve problems and create solutions. The aim of this research is to determine the effect of Team Building Training on improving cognitive and psychomotor aspects related to effective communication in diploma III students of the North Kalimantan Nursing Polytechnic. Quantitative research with a quasi-experimental design is this research method. From the research results, it is known that students who took part in team building training experienced an increase in effective communication by 85.7% in the cognitive aspect and 76.2% in the psychomotor aspect. In the control group, students did not experience an increase in percentage. Through the research results, it can be concluded that it is very important to provide a variety of learning methods to nursing students so that they can obtain different learning experiences through experiential learning which is considered capable of building students' self-confidence in carrying out tasks. effective communication.